Sociology of Poverty - Timothy M. Smeeding (Luxembourg Income Study (LIS), 2002)
Sociologists and other social scientists in rich countries have long been concerned with economic and social deprivation. This entry addresses both the nature and causes of poverty from a sociological perspective and the way that sociologists and social scientists have measured poverty in national and cross-national contexts. Sociologists tend to focus on external (to the individual) explanations of poverty, such as those based on place, class, gender, economic power, and related contextual variables. Thus, poverty is almost always relative to place and context. Poverty measurement, social indicators and other measures of deprivation are also discussed in some detail and the most recent relevant literature is cited.
Keywords: 330; Armut; Soziologie